Efficacy and Safety of Stem Cell Transplantation in Rheumatoid Arthritis: A Systematic Review of Trials - Eric Ferdinand; Grady Krisandi; Phoniex Angellia (Indonesian Rheumatology Association, 2023)
Background: Rheumatoid arthritis (RA) is an autoimmune disorder that deteriorates the quality and function of the synovium membrane, resulting in chronic inflammation, pain, and progressive joint destruction. Based on previous clinical research, stem cell transplantation has shown a promising therapeutic effect for RA based on its anti-inflammatory, immunomodulatory, and regenerative properties. This systematic review aims to evaluate the efficacy and safety of stem cell transplantation for rheumatoid arthritis therapy. Methods: A literature search was performed via PubMed, ProQuest, EBSCOHost, EMBASE, SCOPUS, Cochrane, DOAJ, and clinicaltrial.gov databases, selecting studies that evaluated the effect of stem cells on rheumatoid arthritis from inception to April 7, 2023. The Cochrane Risk of Bias was used to assess randomized controlled trials and ROBINS-I was used to assess clinical trials. Results: 7 randomized controlled trials (RCTs) and 12 non-randomized studies involving 682 subjects were included in this review. Stem cell transplantation was related with better outcomes based on significant improvement of the DAS28 score, HAQ score, ACR score, and laboratory parameters. There were no significant changes in safety parameters compared to the baseline value and control group. Fever, flu-like symptoms, nausea, and vomiting were the most frequently reported adverse effects. Nevertheless, this review revealed a moderate risk of bias and high heterogeneity of the efficacy outcomes of RCTs. Conclusion: Stem cell-based therapies provide clinical benefits for rheumatoid arthritis patients with satisfactory safety measures.